Problematika Kurikulum dan Pembelajaran Jarak Jauh terhadap Pendidikan Karakter (Current Research in Education: Conference Series Journal, 2022)
The curriculum has an important role in realizing the nation's future generation. The curriculum is the key to the success of education, so that the nation will advance if the young generation is of high quality and quality. However, there are still various problems in the development of the curriculum, so solutions are needed. This paper aims to identify problems with curriculum and distance learning on character education. This research uses literature review method. Based on the results of the study, it was found that various problems with curriculum and distance learning on character education, namely the character education curriculum have not been implemented properly. Meanwhile, the problem of distance learning on character education leads to the lack of readiness of students, teachers and parents